Evaluation of the competitiveness of fresh tomato - Krivdáné Dorogi , D. A. (International Journal of Horticultural Science, 2022)
The existence of international trade and related trade theory are closely related to competitiveness. The following study focuses on the competitiveness of Hungary, which studies the development of comparative advantage in terms of tomato for fresh consumption among horticultural products. As a consequence, the main objective is whether Hungary has comparative advantage over EU-28 countries in case of fresh market tomato. Data in the study were provided by FAOSTAT database. The study period focuses on results from 2004 to 2019, breaking them down into 5-year (average) cycles. The method chosen was the RCA index group, the most widely recognized and applied index group for calculating comparative advantage. Although Hungary is not a significant vegetable-producing country in Europe, the fruit and vegetable sector accounts for 10-13% of the production value of agriculture. Regarding the results, it can be stated that Hungary does not have comparative advantage in case of tomato products. With respect to values of the tomato sector, the RCA index is in the range of 0